PENGUATAN ENTREPRENEURIAL ORIENTATION PADA UMKM PRODUK PERALATAN RUMAH TANGGA DI INDONESIA - Ratih Indriyani Indriyani; Jonathan Jonathan Jonathan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to examine the effect of social network on entrepreneurial orientation owned by household appliance business actors. This study also aims to examine the influence of entrepreneurial opportunity recognition and entrepreneurial self-efficacy as mediating variables. The type of research used is quantitative research in the survey category with a sample of 100 respondents. Collecting data using a research questionnaire. Data processing techniques use SmartPLS version 3.0. The results of the study show that social network has a positive and significant influence on entrepreneurial orientation through entrepreneurial opportunity recognition and entrepreneurial self-efficacy, while entrepreneurial self-efficacy and entrepreneurial opportunity recognition do not mediate social networks on individual entrepreneurial orientation.